Electrochemical device and electronic device

By adding conductive materials and appropriate adhesives between the negative electrode active material layer of the lithium-ion battery and the current collector, combined with a specific electrolyte, the safety hazards of lithium-ion batteries in high temperature and overcharge states are solved, which significantly increases the risk of lithium-ion batteries. Improves its cyclic expansion performance and overcharge resistance, reducing safety risks.

CN119133361AActive Publication Date: 2024-12-13NINGDE AMPEREX TECHNOLOGY LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411264680.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2020-10-15
Publication Date
2024-12-13
Estimated Expiration
2040-10-15

AI Technical Summary

Technical Problem

Lithium-ion batteries can easily cause overheating, expansion and safety hazards in high temperatures or overcharged states, which may cause accidents such as explosions or combustion.

Method used

The conductive material is introduced between the negative electrode active material layer and the negative electrode current collector. The average particle size of the conductive material is smaller than the average particle size of the negative electrode active material, and a specific weight and type of adhesive is used to combine with an appropriate electrolyte to form a Improve high-temperature cycling expansion performance and overcharge resistance.

Benefits of technology

It significantly improves the high-temperature cycling expansion performance and anti-overcharge performance of the electrochemical device, reduces the safety risks of lithium-ion batteries in high temperature and overcharge states, and prevents the fracture of the negative electrode and the overheating of the chemical reaction.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119133361A_ABST
    Figure CN119133361A_ABST
Patent Text Reader

Abstract

The invention relates to an electrochemical device and an electronic device. Specifically, the present application provides an electrochemical device including a positive electrode, a negative electrode including a negative electrode current collector and a negative electrode active material layer formed on the negative electrode current collector, the negative electrode active material layer including a negative electrode active material, and an electrolyte solution formed on the negative electrode current collector, wherein a conductive material is arranged between the negative electrode active material layer and the negative electrode current collector, the average particle diameter of the conductive material is smaller than that of the negative electrode active material, and the negative electrode active material layer has a specific weight. The electrochemical device provided by the invention has improved high-temperature cycle expansion performance and overcharge resistance.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] This application is a divisional application of the Chinese invention patent application with invention name “Electrochemical Device and Electronic Device”, application number 202011101403.7, and application date October 15, 2020. Technical Field

[0002] The present application relates to the field of energy storage, and in particular to an electrochemical device and an electronic device, in particular a lithium-ion battery. Background Art

[0003] Electrochemical devices (e.g., lithium-ion batteries) have the advantages of high voltage, small size, light weight, high specific capacity, no memory effect, no pollution, low self-discharge and long cycle life, and have been widely used in many fields such as digital products, electric vehicles, hybrid vehicles, etc. With the widespread application of lithium-ion batteries, their safety performance has also received more and more attention.

[0004] The safety hazard of lithium-ion batteries is mainly caused by internal overheating. If the heat generated inside the lithium-ion battery cannot be released quickly, the temperature of the lithium-ion battery will continue to rise, thereby intensifying the chemical reaction inside the lithium-ion battery, and eventually leading to thermal runaway of the lithium-ion battery, until safety accidents such as explosion and combustion occur.

[0005] In view of the above, there is a real need to provide an electrochemical device and an electronic device with improved performance. Summary of the invention

[0006] The embodiments of the present application provide an electrochemical device and an electronic device with improved high temperature cycle expansion performance and overcharge resistance performance to at least some extent solve at least one safety problem existing in the related art.

[0007] In one aspect of the present application, the present application provides an electrochemical device, comprising: a positive electrode, a negative electrode and an electrolyte, wherein the negative electrode comprises a negative electrode current collector and a negative electrode active material layer formed on the negative electrode current collector, wherein the negative electrode active material layer comprises a negative electrode active material, wherein: a conductive material is present between the negative electrode active material layer and the negative electrode current collector, the average particle size of the conductive material is smaller than the average particle size of the negative electrode active material, and the weight per unit area of ​​the negative electrode active material layer is W mg / cm 2 , W is in the range of 3 to 12.

[0008] According to an embodiment of the present application, the average particle size of the conductive material is less than 1 μm.

[0009] According to an embodiment of the present application, the conductive material includes at least one of carbon black, carbon fiber, graphene or carbon nanotubes.

[0010] According to an embodiment of the present application, a binder is further included between the negative electrode active material layer and the negative electrode current collector.

[0011] According to an embodiment of the present application, the adhesive includes at least one of styrene-butadiene rubber, styrene-butyl acrylate copolymer, styrene-(meth)acrylate copolymer, carboxymethyl cellulose, polyvinyl alcohol, sodium polyacrylate, polyvinylidene fluoride, polyimide, polyamideimide or deacetylated chitosan.

[0012] According to an embodiment of the present application, the adhesive includes an evaporable or decomposable organic adhesive.

[0013] According to an embodiment of the present application, the organic binder includes at least one of chitin-chitosan derivatives, fluorine-containing resins, synthetic rubber, polyamide, polyimide, polyolefin or polyacrylic resin.

[0014] According to an embodiment of the present application, the tensile strength of the negative electrode current collector is FN / mm 2 , F is greater than 400 and 100 / 3≤F / W≤150.

[0015] According to an embodiment of the present application, the tensile strength of the negative electrode current collector is FN / mm 2 The density of the negative electrode active material layer is D g / cm 3 , D is in the range of 1.4 to 2.0 and 560≤F×D≤1800.

[0016] According to an embodiment of the present application, the electrolyte includes at least one of the following compounds:

[0017] (a) Propionate esters;

[0018] (b) organic compounds having a cyano group;

[0019] (c) lithium difluorophosphate;

[0020] (d) Compound of formula 1:

[0021]

[0022] in:

[0023] R 1 , R 2 , R 3 , R 4 , R 5 and R 6 are independently hydrogen or C1-C 10 alkyl;

[0024] L1 and L2 are each independently -(CR 7R 8 ) n -;

[0025] R 7 and R 8 are independently hydrogen or C1-C 10 Alkyl; and

[0026] n is 1, 2 or 3.

[0027] According to an embodiment of the present application, the compound of formula 1 includes at least one of the following compounds:

[0028]

[0029] According to an embodiment of the present application, the content of the organic compound having a cyano group is a %, based on the weight of the electrolyte, and a is in the range of 0.1 to 10.

[0030] According to an embodiment of the present application, W and a satisfy: 0.3≤W / a≤20.

[0031] In another aspect of the present application, the present application provides an electronic device, which includes the electrochemical device according to the present application.

[0032] Additional aspects and advantages of the embodiments of the present application will be described, shown, or explained in part in the subsequent description through implementation of the embodiments of the present application. BRIEF DESCRIPTION OF THE DRAWINGS

[0033] The following will briefly describe the drawings necessary for describing the embodiments of the present application or the prior art to facilitate the description of the embodiments of the present application. Obviously, the drawings described below are only some of the embodiments in the present application. For those skilled in the art, without the need for creative work, drawings of other embodiments can still be obtained based on the structures illustrated in these drawings.

[0034] Figure 1 A schematic diagram showing a negative electrode in the electrochemical device of the present application. DETAILED DESCRIPTION

[0035] The embodiments of the present application will be described in detail below. The embodiments of the present application should not be interpreted as limiting the present application.

[0036] Unless expressly stated otherwise, the following terms used herein have the meanings indicated below.

[0037] In the detailed description and claims, a list of items connected by the term "at least one of" may mean any combination of the listed items. For example, if items A and B are listed, the phrase "at least one of A and B" means only A; only B; or A and B. In another example, if items A, B, and C are listed, the phrase "at least one of A, B, and C" means only A; or only B; only C; A and B (excluding C); A and C (excluding B); B and C (excluding A); or all of A, B, and C. Item A may include a single element or multiple elements. Item B may include a single element or multiple elements. Item C may include a single element or multiple elements. The term "at least one of" has the same meaning as the term "at least one of."

[0038] As used herein, the term "alkyl" is expected to be a straight chain saturated hydrocarbon structure with 1 to 20 carbon atoms. "Alkyl" is also expected to be a branched or cyclic hydrocarbon structure with 3 to 20 carbon atoms. When specifying an alkyl with a specific carbon number, it is expected to cover all geometric isomers with that carbon number; therefore, for example, "butyl" means including n-butyl, sec-butyl, isobutyl, tert-butyl and cyclobutyl; "propyl" includes n-propyl, isopropyl and cyclopropyl. Alkyl examples include, but are not limited to methyl, ethyl, n-propyl, isopropyl, cyclopropyl, n-butyl, isobutyl, sec-butyl, tert-butyl, cyclobutyl, n-pentyl, isopentyl, neopentyl, cyclopentyl, methylcyclopentyl, ethylcyclopentyl, n-hexyl, isohexyl, cyclohexyl, n-heptyl, octyl, cyclopropyl, cyclobutyl, norbornyl, etc.

[0039] As used herein, the term "halo" refers to that hydrogen atoms in a group are partially or fully substituted by halogen atoms (eg, fluorine, chlorine, bromine or iodine).

[0040] With the widespread use of electrochemical devices (e.g., lithium-ion batteries), their safety performance has received increasing attention. The safety hazards of electrochemical devices are mainly caused by internal overheating. When an electrochemical device is at high temperature or overcharged, it will overheat inside, resulting in safety hazards such as expansion, deformation, and even explosion.

[0041] In order to solve the above problems, the present application uses a negative electrode active material layer with a specific weight and arranges a tiny conductive material between the negative electrode active material layer and the negative electrode current collector to prevent the negative electrode from breaking during high-temperature cycling or overcharging, so that the capacity of the electrochemical device can be fully extracted, thereby significantly improving the high-temperature cycling expansion performance and anti-overcharging performance of the electrochemical device.

[0042] In one embodiment, the present application provides an electrochemical device comprising a positive electrode, a negative electrode and an electrolyte as described below.

[0043] I. Negative electrode

[0044] The negative electrode includes a negative electrode collector and a negative electrode active material layer formed on one or both surfaces of the negative electrode collector, the negative electrode active material layer containing a negative electrode active material.

[0045] 1. Conductive materials

[0046] One feature of the electrochemical device of the present application is that there is a conductive material between the negative electrode active material layer and the negative electrode current collector, and the average particle size of the conductive material is smaller than the average particle size of the negative electrode active material. As used herein, "conductive material" refers to a material with excellent electrical conductivity.

[0047] The surface of the negative electrode current collector is relatively smooth, and it is difficult for it to adhere to or support materials such as negative electrode active materials. Providing a conductive material between the negative electrode active material layer and the negative electrode current collector can not only improve the conductivity at the interface between the negative electrode current collector and the negative electrode active material layer, but also make the interface blurry, thereby improving the adhesion between the two. Figure 1 As shown, the negative electrode of the electrochemical device of the present application includes a negative electrode active material layer of a negative electrode active material 1, a negative electrode current collector 3, and a conductive material 2 between the negative electrode active material layer and the negative electrode current collector, wherein a portion of the negative electrode active material 1 is sandwiched in the conductive material 2, thereby being firmly supported by the negative electrode current collector 3. In addition, the conductive material is generally aggregated in a direction parallel to the surface of the negative electrode current collector, and is hardly stacked in a direction perpendicular to the negative electrode current collector. In this case, when the average particle size of the conductive material is smaller than the average particle size of the negative electrode active material, the interface containing the conductive material between the negative electrode current collector and the negative electrode active material layer is very thin, which can significantly improve the high temperature cycle expansion performance and overcharge resistance of the electrochemical device.

[0048] In some embodiments, the average particle size of the conductive material is 1 μm or less. In some embodiments, the average particle size of the conductive material is 0.8 μm or less. In some embodiments, the average particle size of the conductive material is 1 μm or less. In some embodiments, the average particle size of the conductive material is 0.5 μm or less. In some embodiments, the average particle size of the conductive material is 0.2 μm or less. In some embodiments, the average particle size of the conductive material is 0.1 μm or less. When the average particle size of the conductive material is within the above range, it helps to further improve the high temperature cycle expansion performance and overcharge resistance of the electrochemical device.

[0049] In some embodiments, the conductive material is located in a region less than 3 μm from the negative electrode current collector. In some embodiments, the conductive material is located in a region less than 2 μm from the negative electrode current collector. In some embodiments, the conductive material is located in a region less than 1 μm from the negative electrode current collector.

[0050] In some embodiments, in a region less than 3 μm from the negative electrode current collector, based on the total volume of the solid component material, the content of the negative electrode active material sandwiched in the conductive material is less than 10 volume %. In some embodiments, in a region less than 3 μm from the negative electrode current collector, based on the total volume of the solid component material, the content of the negative electrode active material sandwiched in the conductive material is less than 8 volume %. In some embodiments, in a region less than 3 μm from the negative electrode current collector, based on the total volume of the solid component material, the content of the negative electrode active material sandwiched in the conductive material is less than 5 volume %.

[0051] In some embodiments, the conductive material has a shape including at least one of granular and fibrous.

[0052] In some embodiments, the conductive material comprises at least one of carbon black, carbon fiber, graphene, or carbon nanotubes. In some embodiments, the carbon black comprises at least one of acetylene black, furnace black, or Ketjen black.

[0053] 2. Adhesive

[0054] In some embodiments, a binder is further included between the negative electrode active material layer and the negative electrode current collector. The binder can improve the bonding between the negative electrode active material layer and the negative electrode current collector. The binder that can be used is generally a resin having the following properties: no decomposition occurs during the preparation of the negative electrode, has redox resistance, can follow the volume expansion of the electrochemical device during charging and discharging, and prevents the interface between the negative electrode current collector and the negative electrode active material layer from being broken due to the expansion and contraction of the negative electrode active material layer.

[0055] In some embodiments, the binder includes at least one of styrene-butadiene rubber, styrene-butyl acrylate copolymer, styrene-(meth)acrylate copolymer, carboxymethyl cellulose, polyvinyl alcohol, sodium polyacrylate, polyvinylidene fluoride, polyimide, polyamideimide, or deacetylated chitosan.

[0056] In some embodiments, the binder includes an evaporable or decomposable organic binder. In some embodiments, the organic binder evaporates or decomposes in the range of 160°C to 500°C. In some embodiments, the organic binder evaporates or decomposes in the range of 200°C to 400°C. In some embodiments, the organic binder evaporates or decomposes in the range of 200°C to 300°C. In the process of preparing the negative electrode, the negative electrode active material layer is usually coated at a temperature below 120°C, so the above-mentioned organic binder will not evaporate or decompose in the coating process. The above-mentioned organic binder can improve the closeness between the negative electrode current collector and the negative electrode active material layer at room temperature. When the above-mentioned temperature is reached, the organic binder evaporates or decomposes, thereby electrically isolating the negative electrode current collector from the negative electrode active material layer, and insulating the negative electrode current collector from the negative electrode active material layer, thereby preventing the electrochemical device from continuing to react chemically and overheating, and improving the high-temperature storage expansion and overcharge resistance of the electrochemical device.

[0057] As used herein, the terms "evaporation" and "decomposition" refer to the organic binder starting to undergo deterioration such that at least a portion of it ceases to exist, and the term "electrical isolation" means a state in which a gap is generated in the original occupied position of the organic binder after evaporation or decomposition. When electrical isolation occurs between the negative electrode current collector and the negative electrode active material layer, the content of the organic binder is reduced by 15% to 20%, or the resistance value between the negative electrode current collector and the negative electrode active material layer reaches 300Ω to 1000Ω in terms of the two-terminal surface resistance of the electrode.

[0058] In some embodiments, the organic binder includes at least one of chitin-chitosan derivatives, fluorine-containing resins, synthetic rubbers, polyamides, polyimides, polyolefins, or polyacrylic resins.

[0059] In some embodiments, the chitin-chitosan derivative comprises at least one of hydroxyethyl chitosan, hydroxypropyl chitosan, hydroxybutyl chitosan, or alkylated chitosan.

[0060] In some embodiments, the fluorine-containing resin includes at least one of polyvinylidene fluoride or polytetrafluoroethylene.

[0061] In some embodiments, the synthetic rubber includes at least one of styrene-butadiene rubber, acrylic rubber, or nitrile rubber.

[0062] In some embodiments, the polyolefin includes at least one of low density polyethylene, high density polyethylene, or polypropylene.

[0063] In some embodiments, the polyacrylic resin includes at least one of ethylene glycol dimethacrylate or propylene glycol dimethacrylate.

[0064] In some embodiments, the alkylated chitosan comprises an organic binder made by mixing and cross-linking organic acids, wherein the organic acid comprises at least one of salicylic acid, pyromellitic acid, citric acid or trimellitic acid.

[0065] The negative electrode active material can be supported by the minute conductive material, that is, the minute conductive material can improve the adhesion between the negative electrode current collector and the negative electrode active material layer. Therefore, a small amount of binder can exist between the negative electrode active material layer and the negative electrode current collector.

[0066] 3. Negative electrode active material layer

[0067] The negative electrode active material layer may be one or more layers, and each layer of the multiple layers of negative electrode active material may contain the same or different negative electrode active materials. The negative electrode active material is any material that can reversibly embed and deintercalate metal ions such as lithium ions. In some embodiments, the chargeable capacity of the negative electrode active material is greater than the discharge capacity of the positive electrode active material to prevent lithium metal from being accidentally precipitated on the negative electrode during charging.

[0068] Another feature of the electrochemical device of the present application is that the weight per unit area of ​​the negative electrode active material layer is W mg / cm 2 , W is in the range of 3 to 12. In some embodiments, W is in the range of 5 to 10. In some embodiments, W is in the range of 6 to 8. In some embodiments, W is 3, 4, 5, 6, 7, 8, 9, 10, 11, 12 or in the range consisting of any two of the above values. When the weight per unit area of ​​the negative electrode active material layer is within the above range, it helps to improve the permeability of the electrolyte to the interface between the negative electrode current collector and the negative electrode active material layer, improve the electron transport in the electrochemical device, and at the same time reduce the impact on the active material layer during processing, so that the interface between the negative electrode current collector and the negative electrode active material layer is maintained in good condition, and the relative displacement between the negative electrode active materials is reduced, thereby improving the high temperature storage expansion performance and anti-overcharge performance of the electrochemical device.

[0069] The weight per unit area of ​​the negative electrode active material layer in this application is the mass (mg) of the negative electrode active material layer relative to the area (cm 2 ) ratio. The mass and area of ​​the negative electrode active material layer are obtained by the following method: cut a test piece of appropriate size from the negative electrode, measure its area as S1 and mass W0, then peel the negative electrode current collector from the negative electrode, measure the mass W1 of the negative electrode current collector, and calculate the mass of the negative electrode active material layer from (W0-W1), and the weight per unit area = (W0-W1) / S1. If the selected negative electrode is a double-sided active material layer, the weight per unit area = (W0-W1) / S1 / 2.

[0070] Examples of a method for peeling the negative electrode active material layer include immersing the negative electrode active material layer in a solvent that can dissolve or swell the negative electrode active material layer, and wiping the active material layer with a cloth or the like.

[0071] The weight per unit area of ​​the negative electrode active material layer can be adjusted by a known method. For example, when the negative electrode active material layer is formed by coating, it can be adjusted by changing the solid content concentration of the coating liquid used to form the negative electrode active material layer, the number of coatings, the gap between the coating liquid inlet of the coating machine, etc. The weight per unit area of ​​the negative electrode active material layer can be increased by increasing the solid content concentration, increasing the number of coatings, or increasing the gap. The weight per unit area of ​​the negative electrode active material layer can be reduced by reducing the solid content concentration, reducing the number of coatings, or reducing the gap.

[0072] In some embodiments, the density of the negative electrode active material layer is 1.0 g / cm 3 Up to 2.0g / cm 3 In some embodiments, the density of the negative electrode active material layer is 1.2 g / cm 3 Up to 1.9g / cm 3 In some embodiments, the density of the negative electrode active material layer is 1.3 g / cm 3 Up to 1.8g / cm 3 In some embodiments, the density of the negative electrode active material layer is 1.5 g / cm 3 Up to 1.7g / cm 3 In some embodiments, the density of the negative electrode active material layer is 1.0 g / cm 3 , 1.1g / cm 3 , 1.2g / cm 3 , 1.3g / cm 3 , 1.4g / cm 3 , 1.5g / cm 3 , 1.6g / cm 3 , 1.7g / cm 3 , 1.8g / cm 3 , 1.9g / cm 3 , 2.0g / cm 3 Or within the range formed by any two of the above values. When the density of the negative electrode active material layer is within the above range, the negative electrode active material is not easily destroyed, and a relatively low initial irreversible capacity can be maintained, so that the negative electrode active materials maintain high conductivity, and at the same time, the permeability of the electrolyte to the interface between the negative electrode current collector and the negative electrode active material layer can be improved, thereby helping to improve the high temperature storage expansion performance and overcharge resistance of the electrochemical device.

[0073] In some embodiments, the negative electrode active material includes, but is not limited to, graphite, hard carbon, soft carbon, MCMB and other carbon materials, silicon, SiO x Silicon compounds such as silicon oxide represented by (0<x<2), metallic lithium, metals forming alloys with lithium and alloys thereof, amorphous compounds mainly composed of oxides such as tin dioxide, and lithium titanate (Li4Ti5O 12 ).

[0074] In some embodiments, metals that form alloys with metallic lithium include, but are not limited to, aluminum, silicon, tin, germanium, and the like.

[0075] In some embodiments, the negative electrode active material is a metal or semi-metal that forms an alloy with lithium, represented by silicon, and their alloys, which have high charge and discharge capacity.

[0076] In some embodiments, the negative electrode active material includes a mixture of a metal or semi-metal that forms an alloy with lithium, represented by silicon, and an alloy thereof, and a carbon material having a graphite structure.

[0077] In some embodiments, the negative electrode active material comprises a carbon material. In some embodiments, the negative electrode active material comprises a carbon material having a graphite structure. In some embodiments, the negative electrode active material is at least one of artificial graphite or natural graphite.

[0078] In some embodiments, the negative electrode active material includes different components, wherein the carbon material having a graphite structure is predominant. In some embodiments, the content of the carbon material having a graphite structure is 70.0% or more based on the weight of the negative electrode active material layer. In some embodiments, the content of the carbon material having a graphite structure is 90.0% or more based on the weight of the negative electrode active material layer. The content of the carbon material having a graphite structure is 95.0% or more based on the weight of the negative electrode active material layer.

[0079] In some embodiments, the carbon material has a median particle size (D50) of about 5 μm to about 30 μm. In some embodiments, the carbon material has a median particle size (D50) of about 10 μm to about 25 μm. In some embodiments, the carbon material has a median particle size (D50) of about 15 μm to about 20 μm. In some embodiments, the carbon material has a median particle size (D50) of about 3 μm, about 5 μm, about 7 μm, about 10 μm, about 15 μm, about 20 μm, about 25 μm, about 30 μm, or a median particle size (D50) within the range of any two of the above values. When the median particle size of the carbon material is within the above range, the irreversible capacity of the electrochemical device is small and it is easy to evenly coat the negative electrode. The median particle size (D50) of the carbon material refers to the volume-based average particle size obtained by the laser diffraction / scattering method, which can be measured by the following method: the carbon material is dispersed in a 0.2% aqueous solution (about 10 mL) of polyoxyethylene (20) sorbitan monolaurate and tested using a laser diffraction / scattering particle size distribution meter (LA-700 manufactured by Horiba, Ltd.).

[0080] In some embodiments, the negative electrode active material layer includes a negative electrode binder, which can improve the bonding between the negative electrode active materials. The type of negative electrode binder is not particularly limited, as long as it is a material that is stable to the solvent used in the electrolyte or electrode manufacturing. The negative electrode binder may include a polymer material that can be dissolved or dispersed in the solvent used to manufacture the negative electrode. In the case of using an aqueous solvent when manufacturing the negative electrode, the water-soluble (water-soluble) polymer material includes, but is not limited to, cellulose polymers such as carboxymethyl cellulose (CMC), methyl cellulose (MC), cellulose acetate phthalate (CAP), hydroxypropyl methyl cellulose (HPMC); and polyvinyl alcohol (PVA), etc. Polymer materials that can be dispersed in water (water-dispersible) include, but are not limited to, vinyl polymers such as polyethylene (PE) and polypropylene (PP); fluorine-based resins such as polyethylene oxide (PEO), polytetrafluoroethylene (PTFE), tetrafluoroethylene-hexafluoropropylene copolymer (FEP), and tetrafluoroethylene-perfluoroalkyl vinyl ether copolymer (PFA); vinyl acetate copolymers; and rubbers such as styrene-butadiene rubber (SBR) and acrylic modified SBR resin (SBR latex), etc.

[0081] In some embodiments, the content of the binder is 8 parts by mass or less relative to 100 parts by mass of the negative electrode active material. In some embodiments, the content of the binder is 7 parts by mass or less relative to 100 parts by mass of the negative electrode active material. In some embodiments, the content of the binder is 6 parts by mass or less relative to 100 parts by mass of the negative electrode active material. In some embodiments, the content of the binder is 5 parts by mass or less relative to 100 parts by mass of the negative electrode active material. In some embodiments, the content of the binder is 4 parts by mass or less relative to 100 parts by mass of the negative electrode active material. In some embodiments, the content of the binder is 3 parts by mass or less relative to 100 parts by mass of the negative electrode active material. In some embodiments, the content of the binder is 2 parts by mass or less relative to 100 parts by mass of the negative electrode active material.

[0082] The thickness of the negative electrode active material layer refers to the thickness of the negative electrode active material layer coated on a single side of the negative electrode current collector. In some embodiments, the thickness of the negative electrode active material layer is 15 μm or more. In some embodiments, the thickness of the negative electrode active material layer is 20 μm or more. In some embodiments, the thickness of the negative electrode active material layer is 30 μm or more. In some embodiments, the thickness of the negative electrode active material layer is 150 μm or less. In some embodiments, the thickness of the negative electrode active material layer is 120 μm or less. In some embodiments, the thickness of the negative electrode active material layer is 100 μm or less. In some embodiments, the thickness of the negative electrode active material layer is within the range consisting of any two of the above values. When the thickness of the negative electrode active material layer is within the above range, the electrolyte can penetrate into the vicinity of the interface of the negative electrode current collector, thereby improving the charge and discharge characteristics of the electrochemical device at high current density; at the same time, the volume ratio of the negative electrode current collector to the negative electrode active material is within an appropriate range, which can ensure the capacity of the electrochemical device.

[0083] 3. Negative electrode current collector

[0084] In some embodiments, the tensile strength of the negative electrode current collector is FN / mm 2, F is greater than 400. In some embodiments, F is greater than 450. In some embodiments, F is greater than 500. In some embodiments, F is greater than 550. In some embodiments, F is greater than 600. In some embodiments, F is greater than 650. In some embodiments, F is greater than 700. In some embodiments, F is greater than 800. In some embodiments, F is greater than 900. In some embodiments, F is greater than 1000. As used herein, the term "tensile strength" refers to the ratio of the maximum tensile force required for the sample to break to the cross-sectional area of ​​the sample. The use of a negative current collector with high tensile strength can inhibit the cracking of the negative current collector caused by the expansion / contraction of the negative active material layer during charging / discharging of the electrochemical device, thereby significantly improving the high temperature cycle expansion performance and overcharge resistance of the electrochemical device.

[0085] In some embodiments, the tensile strength of the negative electrode current collector is FN / mm 2 The weight per unit area of ​​the negative electrode active material layer is W mg / cm 2 Satisfies: 100 / 3≤F / W≤150. In some embodiments, 40≤F / W≤120. In some embodiments, 50≤F / W≤100. In some embodiments, 60≤F / W≤80. In some embodiments, F / W is 100 / 3, 40, 50, 60, 70, 80, 90, 100, 110, 120, 130, 140, 150 or within a range consisting of any two of the above values. When the tensile strength of the negative electrode current collector is FN / mm 2 The weight per unit area of ​​the negative electrode active material layer is W mg / cm 2 When the above relationship is met, the high temperature cycle expansion performance and overcharge resistance of the electrochemical device can be further improved.

[0086] The tensile strength of the negative electrode current collector can be measured using the same device and method as that for measuring elongation (refer to the test method of GB-228-87).

[0087] In some embodiments, the density of the negative electrode active material layer is D g / cm 3 , D is in the range of 1.4 to 2.0. In some embodiments, D is in the range of 1.5 to 1.8. In some embodiments, D is 1.4, 1.5, 1.6, 1.7, 1.8, 1.9, 2.0 or in the range consisting of any two of the above values. When the density of the negative electrode active material layer is within the above range, the negative electrode active material is not easily destroyed, and a low initial irreversible capacity can be maintained, so that the negative electrode active materials maintain high conductivity, and at the same time, the permeability of the electrolyte to the interface between the negative electrode current collector and the negative electrode active material layer can be improved, thereby helping to improve the high temperature cycle expansion performance and overcharge resistance of the electrochemical device.

[0088] In some embodiments, the tensile strength of the negative electrode current collector is FN / mm 2 Density of the negative electrode active material layer D g / cm 3 Satisfies: 560≤F×D≤1800. In some embodiments, 600≤F×D≤1500. In some embodiments, 700≤F×D≤1200. In some embodiments, 600≤F×D≤1500. In some embodiments, 800≤F×D≤1000. In some embodiments, F×D is 560, 600, 700, 800, 900, 1000, 1100, 1200, 1300, 1400, 1500, 1600, 1700, 1800 or within the range of any two of the above values. When the tensile strength of the negative electrode current collector is FN / mm 2 Density of the negative electrode active material layer D g / cm 3 When the above relationship is met, the high temperature cycle expansion performance and overcharge resistance of the electrochemical device can be further improved.

[0089] In some embodiments, the negative electrode current collector includes, but is not limited to, metal foil, metal cylinder, metal strip, metal plate, metal film, metal mesh, stamped metal, foamed metal, etc. In some embodiments, the negative electrode current collector is metal foil. In some embodiments, the negative electrode current collector is copper foil. As used herein, the term "copper foil" includes copper alloy foil.

[0090] In some embodiments, the negative electrode current collector is a conductive resin. In some embodiments, the conductive resin comprises a film obtained by evaporating copper on a polypropylene film.

[0091] Preparation of negative electrode

[0092] The negative electrode in the electrochemical device of the present application can be prepared by any known method. For example, a binder, a solvent, a thickener, a conductive material, a filler, etc. are added to the negative electrode active material to prepare a slurry, and the slurry is applied to the negative electrode current collector, and the electrode is formed by pressing after drying. The negative electrode active material can also be roll-formed into a sheet electrode, or compressed into a particle electrode.

[0093] II. Electrolyte

[0094] The electrolyte used in the electrochemical device of the present application includes an electrolyte and a solvent that dissolves the electrolyte. In some embodiments, the electrolyte used in the electrochemical device of the present application further includes an additive.

[0095] According to some embodiments of the present application, the electrolyte further includes at least one of the following compounds:

[0096] (a) Propionate esters;

[0097] (b) organic compounds having a cyano group;

[0098] (c) Lithium difluorophosphate

[0099] (d) Compound of formula 1:

[0100]

[0101] in:

[0102] R 1 , R 2 , R 3 , R 4 , R 5 and R 6 are independently hydrogen or C1-C 10 alkyl;

[0103] L1 and L2 are each independently -(CR 7 R 8 ) n -;

[0104] R 7 and R 8 are independently hydrogen or C1-C 10 Alkyl; and

[0105] n is 1, 2 or 3.

[0106] (a) Propionate

[0107] According to some embodiments of the present application, the propionate comprises a compound of formula 2:

[0108]

[0109] in:

[0110] R 1 Selected from ethyl or halogenated ethyl,

[0111] R 2 Selected from C1-C6 alkyl or C1-C6 haloalkyl.

[0112] In certain embodiments, the propionic ester includes, but is not limited to, methyl propionate, ethyl propionate, propyl propionate, butyl propionate, pentyl propionate, methyl halogenated propionate, ethyl halogenated propionate, propyl halogenated propionate, butyl halogenated propionate and pentyl halogenated propionate. In certain embodiments, the propionic ester is selected from at least one of methyl propionate, ethyl propionate, propyl propionate, butyl propionate and pentyl propionate. In certain embodiments, the halogen group in the methyl halogenated propionate, ethyl halogenated propionate, propyl halogenated propionate, butyl halogenated propionate and pentyl halogenated propionate is selected from one or more of fluorine group (-F), chlorine group (-Cl), bromine group (-Br) and iodine group (-I). In certain embodiments, the halogen group is a fluorine group (-F), which can achieve a more excellent effect.

[0113] In some embodiments, the content of the propionate ester is 10% to 65% based on the weight of the electrolyte. In some embodiments, the content of the propionate ester is 15% to 60% based on the weight of the electrolyte. In some embodiments, the content of the propionate ester is 30% to 50% based on the weight of the electrolyte. In some embodiments, the content of the propionate ester is 30% to 40% based on the weight of the electrolyte. In some embodiments, the content of the propionate ester is 10%, 15%, 20%, 25%, 30%, 35%, 40%, 45%, 50%, 55%, 60%, 65% or in a range consisting of any two of the above values ​​based on the weight of the electrolyte. Using propionate esters with the above content can achieve better results.

[0114] (b) Compounds having a cyano group

[0115] In some embodiments, the compound having a cyano group includes, but is not limited to, one or more of the following: succinonitrile, glutaronitrile, adiponitrile, 1,5-dicyanopentane, 1,6-dicyanohexane, tetramethylsuccinonitrile, 2-methylglutaronitrile, 2,4-dimethylglutaronitrile, 2,2,4,4-tetramethylglutaronitrile, 1,4-dicyanopentane, 1,2-dicyanobenzene, 1,3-dicyanobenzene, 1,4-dicyanobenzene, ethylene glycol bis(propionitrile) ether, 3,5-dioxa-heptanenitrile, 1,4-bis(cyanoethoxy)butane, diethylene glycol di(2-cyanoethyl)ether, triethylene glycol di(2-cyanoethyl)ether, tetraethylene glycol di(2-cyanoethyl)ether, 1,3-bis(2-cyanoethoxy)propane, 1,4-bis(2-cyanoethoxy)butane, 1,5-bis(2-cyanoethoxy)pentane, ethylene glycol di(4-cyanobutyl)ether, 1,4-dicyano-2-butene, 1,4-dicyano-2-methyl-2-butene, 1,4-dicyano-2-ethyl-2-butene, 1,4-dicyano-2,3-dimethyl-2-butene, 1,4-dicyano-2,3-diethyl-2-butene, 1,6-dicyano-3-hexene, 1,6-dicyano-2-methyl-3-hexene, 1,3,5-pentanetricarbonitrile, 1,2,3-propanetricarbonitrile, 1,3,6-hexatriconitrile, 1,2,6-hexatriconitrile , 1,2,3-tris(2-cyanoethoxy)propane, 1,2,4-tris(2-cyanoethoxy)butane, 1,1,1-tris(cyanoethoxymethylene)ethane, 1,1,1-tris(cyanoethoxymethylene)propane, 3-methyl-1,3,5-tris(cyanoethoxy)pentane, 1,2,7-tris(cyanoethoxy)heptane, 1,2,6-tris(cyanoethoxy)hexane and 1,2,5-tris(cyanoethoxy)pentane.

[0116] The above compounds having a cyano group can be used alone or in any combination. If the electrolyte contains two or more compounds having a cyano group, the content of the compound having a cyano group refers to the total content of the two or more compounds having a cyano group.

[0117] In some embodiments, the content of the organic compound having a cyano group is a%, based on the weight of the electrolyte, and a is in the range of 0.1 to 10. In some embodiments, a is in the range of 0.1 to 8. In some embodiments, a is in the range of 0.5 to 5. In some embodiments, a is in the range of 1 to 3. In some embodiments, a is 0.1, 0.5, 0.8, 1, 1.5, 2, 2.5, 3, 3.5, 4, 4.5, 5, 5.5, 6, 6.5, 7, 7.5, 8, 8.5, 9, 9.5, 10 or in the range consisting of any two of the above values. When the content of the compound having a cyano group in the electrolyte is within the above range, it helps to further improve the high temperature cycle expansion performance and overcharge resistance of the electrochemical device.

[0118] In some embodiments, the weight per unit area of ​​the negative electrode active material layer is W mg / cm 2 The content of the compound having a cyano group in the electrolyte is b% and satisfies: 0.3≤W / a≤20. In some embodiments, 0.5≤W / a≤15. In some embodiments, 1≤W / a≤10. In some embodiments, 3≤W / a≤5. In some embodiments, W / a is 0.3, 0.5, 1, 3, 5, 8, 10, 13, 15, 18, 20 or in the range consisting of any two of the above values. When the weight per unit area of ​​the negative electrode active material layer is W mg / cm 2 When the content of the compound having a cyano group in the electrolyte is b% and the above relationship is satisfied, it helps to further improve the high-temperature cycle expansion performance and overcharge resistance of the electrochemical device.

[0119] (c) Lithium difluorophosphate (LiPO2F2)

[0120] In some embodiments, the content of lithium difluorophosphate is 0.01% to 1.5% based on the weight of the electrolyte. In some embodiments, the content of lithium difluorophosphate is 0.05% to 1.2% based on the weight of the electrolyte. In some embodiments, the content of lithium difluorophosphate is 0.1% to 1.0% based on the weight of the electrolyte. In some embodiments, the content of lithium difluorophosphate is 0.5% to 0.8% based on the weight of the electrolyte. In some embodiments, the content of lithium difluorophosphate is 0.01%, 0.05%, 0.1%, 0.15%, 0.2%, 0.25%, 0.3%, 0.35%, 0.4%, 0.45%, 0.5%, 0.8%, 1%, 1.5% or in the range of any two of the above values ​​based on the weight of the electrolyte.

[0121] (d) Compound of formula 1

[0122] In some embodiments, the compound of Formula 1 includes at least one of the following compounds:

[0123]

[0124]

[0125] In some embodiments, the content of the compound of formula 1 is 0.01% to 5% based on the weight of the electrolyte. In some embodiments, the content of the compound of formula 1 is 0.05% to 3% based on the weight of the electrolyte. In some embodiments, the content of the compound of formula 1 is 0.1% to 2% based on the weight of the electrolyte. In some embodiments, the content of the compound of formula 1 is 0.5% to 1% based on the weight of the electrolyte. In some embodiments, the content of the compound of formula 1 is 0.01%, 0.05%, 0.1%, 0.5%, 1%, 2%, 3%, 4%, 5% or in the range of any two of the above values ​​based on the weight of the electrolyte.

[0126] Solvents

[0127] In some embodiments, the electrolyte further comprises any non-aqueous solvent known in the prior art that can be used as a solvent for the electrolyte.

[0128] In some embodiments, the non-aqueous solvent includes, but is not limited to, one or more of the following: cyclic carbonates, chain carbonates, cyclic carboxylates, chain carboxylates, cyclic ethers, chain ethers, phosphorus-containing organic solvents, sulfur-containing organic solvents, and aromatic fluorine-containing solvents.

[0129] In some embodiments, examples of the cyclic carbonate may include, but are not limited to, one or more of the following: ethylene carbonate (EC), propylene carbonate (PC) and butylene carbonate. In some embodiments, the cyclic carbonate has 3-6 carbon atoms.

[0130] In some embodiments, examples of the linear carbonates may include, but are not limited to, one or more of the following: dimethyl carbonate, ethyl methyl carbonate, diethyl carbonate (DEC), methyl n-propyl carbonate, ethyl n-propyl carbonate, di-n-propyl carbonate, etc. Examples of fluorine-substituted linear carbonates may include, but are not limited to, one or more of the following: bis(fluoromethyl) carbonate, bis(difluoromethyl) carbonate, bis(trifluoromethyl) carbonate, bis(2-fluoroethyl) carbonate, bis(2,2-difluoroethyl) carbonate, bis(2,2,2-trifluoroethyl) carbonate, 2-fluoroethyl methyl carbonate, 2,2-difluoroethyl methyl carbonate, and 2,2,2-trifluoroethyl methyl carbonate, etc.

[0131] In some embodiments, examples of the cyclic carboxylic acid ester may include, but are not limited to, one or more of the following: one or more of γ-butyrolactone and γ-valerolactone. In some embodiments, part of the hydrogen atoms of the cyclic carboxylic acid ester may be substituted with fluorine.

[0132] In some embodiments, examples of the chain carboxylic acid esters may include, but are not limited to, one or more of the following: methyl acetate, ethyl acetate, propyl acetate, isopropyl acetate, butyl acetate, sec-butyl acetate, isobutyl acetate, tert-butyl acetate, methyl propionate, ethyl propionate, propyl propionate, isopropyl propionate, methyl butyrate, ethyl butyrate, propyl butyrate, methyl isobutyrate, ethyl isobutyrate, methyl valerate, ethyl valerate, methyl pivalate and ethyl pivalate, etc. In some embodiments, some hydrogen atoms of the chain carboxylic acid ester may be substituted by fluorine. In some embodiments, examples of fluorine-substituted chain carboxylic acid esters may include, but are not limited to, methyl trifluoroacetate, ethyl trifluoroacetate, propyl trifluoroacetate, butyl trifluoroacetate and 2,2,2-trifluoroethyl trifluoroacetate, etc.

[0133] In some embodiments, examples of the cyclic ether may include, but are not limited to, one or more of the following: tetrahydrofuran, 2-methyltetrahydrofuran, 1,3-dioxolane, 2-methyl1,3-dioxolane, 4-methyl1,3-dioxolane, 1,3-dioxane, 1,4-dioxane and dimethoxypropane.

[0134] In some embodiments, examples of the chain ether may include, but are not limited to, one or more of the following: dimethoxymethane, 1,1-dimethoxyethane, 1,2-dimethoxyethane, diethoxymethane, 1,1-diethoxyethane, 1,2-diethoxyethane, ethoxymethoxymethane, 1,1-ethoxymethoxyethane and 1,2-ethoxymethoxyethane, etc.

[0135] In some embodiments, examples of the phosphorus-containing organic solvent may include, but are not limited to, one or more of the following: trimethyl phosphate, triethyl phosphate, dimethyl ethyl phosphate, diethyl methyl phosphate, ethylidene methyl phosphate, ethylidene ethyl phosphate, triphenyl phosphate, trimethyl phosphite, triethyl phosphite, triphenyl phosphite, tris(2,2,2-trifluoroethyl) phosphate, and tris(2,2,3,3,3-pentafluoropropyl) phosphate, etc.

[0136] In some embodiments, examples of the sulfur-containing organic solvent may include, but are not limited to, one or more of the following: sulfolane, 2-methylsulfolane, 3-methylsulfolane, dimethyl sulfone, diethyl sulfone, ethyl methyl sulfone, methyl propyl sulfone, dimethyl sulfoxide, methyl methanesulfonate, ethyl methanesulfonate, methyl ethanesulfonate, ethyl ethanesulfonate, dimethyl sulfate, diethyl sulfate, and dibutyl sulfate. In some embodiments, some hydrogen atoms of the sulfur-containing organic solvent may be substituted by fluorine.

[0137] In some embodiments, the aromatic fluorine-containing solvent includes, but is not limited to, one or more of the following: fluorobenzene, difluorobenzene, trifluorobenzene, tetrafluorobenzene, pentafluorobenzene, hexafluorobenzene, and trifluoromethylbenzene.

[0138] In some embodiments, the solvent used in the electrolyte of the present application includes cyclic carbonates, chain carbonates, cyclic carboxylates, chain carboxylates, and combinations thereof. In some embodiments, the solvent used in the electrolyte of the present application includes an organic solvent selected from the group consisting of the following substances: ethylene carbonate, propylene carbonate, diethyl carbonate, ethyl propionate, propyl propionate, n-propyl acetate, ethyl acetate, and combinations thereof. In some embodiments, the solvent used in the electrolyte of the present application includes: ethylene carbonate, propylene carbonate, diethyl carbonate, ethyl propionate, propyl propionate, γ-butyrolactone, and combinations thereof.

[0139] additive

[0140] In some embodiments, examples of the additive may include, but are not limited to, one or more of the following: fluorocarbonate, ethylene carbonate containing a carbon-carbon double bond, a compound containing a sulfur-oxygen double bond, and an acid anhydride.

[0141] In some embodiments, the additive is present in an amount of 0.01% to 15%, 0.1% to 10%, or 1% to 5%, based on the weight of the electrolyte.

[0142] According to an embodiment of the present application, based on the weight of the electrolyte, the content of the propionate is 1.5 to 30 times, 1.5 to 20 times, 2 to 20 times, or 5 to 20 times that of the additive.

[0143] In some embodiments, the additive comprises one or more fluorocarbonates. During the charging / discharging of the lithium-ion battery, the fluorocarbonates can work together with the propionate to form a stable protective film on the surface of the negative electrode, thereby inhibiting the decomposition reaction of the electrolyte.

[0144] In some embodiments, the fluorinated carbonate has the formula C=O(OR x )(OR y ), where R x and R y Each is selected from an alkyl or halogenated alkyl group having 1 to 6 carbon atoms, wherein R x and R y At least one of them is selected from a fluoroalkyl group having 1 to 6 carbon atoms, and R x and R y Optionally together with the atoms to which it is attached, it forms a 5- to 7-membered ring.

[0145] In some embodiments, examples of the fluorinated carbonates may include, but are not limited to, one or more of the following: fluoroethylene carbonate, cis-4,4-difluoroethylene carbonate, trans-4,4-difluoroethylene carbonate, 4,5-difluoroethylene carbonate, 4-fluoro-4-methylethylene carbonate, 4-fluoro-5-methylethylene carbonate, trifluoromethyl methyl carbonate, trifluoroethyl methyl carbonate, and ethyl trifluoroethyl carbonate, etc.

[0146] In some embodiments, the additive comprises one or more ethylene carbonates containing carbon-carbon double bonds. Examples of the ethylene carbonates containing carbon-carbon double bonds may include, but are not limited to, one or more of the following: vinylene carbonate, methyl vinylene carbonate, ethyl vinylene carbonate, 1,2-dimethyl vinylene carbonate, 1,2-diethyl vinylene carbonate, fluoro vinylene carbonate, trifluoromethyl vinylene carbonate; vinyl ethylene carbonate, 1-methyl-2-vinyl ethylene carbonate, 1-ethyl-2-vinyl ethylene carbonate, 1-n-propyl-2-vinyl ethylene carbonate, 1-methyl-2-vinyl ethylene carbonate, 1,1-divinyl ethylene carbonate, 1,2-divinyl ethylene carbonate, 1,1-dimethyl-2-methylene ethylene carbonate and 1,1-diethyl-2-methylene ethylene carbonate, etc. In some embodiments, the ethylene carbonate containing carbon-carbon double bonds includes vinylene carbonate, which is easy to obtain and can achieve more excellent effects.

[0147] In some embodiments, the additive is a combination of fluorocarbonic acid ester and ethylene carbonate containing carbon-carbon double bonds. In some embodiments, the additive is a combination of fluorocarbonic acid ester and a compound containing sulfur-oxygen double bonds. In some embodiments, the additive is a combination of fluorocarbonic acid ester and an organic compound with a cyano group. In some embodiments, the additive is a combination of fluorocarbonic acid ester and cyclic carboxylic acid ester. In some embodiments, the additive is a combination of fluorocarbonic acid ester and cyclic phosphoric acid anhydride. In some embodiments, the additive is a combination of fluorocarbonic acid ester and carboxylic acid anhydride. In some embodiments, the additive is a combination of fluorocarbonic acid ester and sulfonic acid anhydride. In some embodiments, the additive is a combination of fluorocarbonic acid ester and carboxylic acid sulfonic acid anhydride.

[0148] Electrolytes

[0149] The electrolyte is not particularly limited, and any substance known as an electrolyte can be used arbitrarily. In the case of a lithium secondary battery, a lithium salt is generally used. Examples of the electrolyte may include, but are not limited to, inorganic lithium salts such as LiPF6, LiBF4, LiClO4, LiAlF4, LiSbF6, and LiWF7; lithium tungstates such as LiWOF5; lithium carboxylates such as HCO2Li, CH3CO2Li, CH2FCO2Li, CHF2CO2Li, CF3CO2Li, CF3CH2CO2Li, CF3CF2CO2Li, CF3CF2CF2CO2Li, and CF3CF2CF2CF2CO2Li; lithium salts such as FSO3Li, CH3SO3Li 、CH2FSO3Li、CHF2SO3Li、CF3SO3Li、CF3CF2SO3Li、CF3CF2CF2SO3Li、CF3CF2CF2CF2SO3Li and other lithium sulfonate salts; LiN(FCO)2、LiN(FCO)(FSO2)、LiN(FSO2)2、LiN(FSO2)(CF3SO2)、LiN(CF3SO2)2、LiN(C2F5SO2)2、Cyclic 1,2-perfluoroethane bissulfonyl imide lithium、Cyclic 1,3-perfluoropropane bissulfonyl imide Lithium, LiN(CF3SO2)(C4F9SO2) and other imide lithium salts; LiC(FSO2)3, LiC(CF3SO2)3, LiC(C2F5SO2)3 and other methylated lithium salts; (malonate) borate lithium salts such as bis(malonate) borate and difluoro(malonate) borate lithium salts; (malonate) phosphate lithium salts such as tris(malonate) phosphate, difluorobis(malonate) phosphate, tetrafluoro(malonate) phosphate; and LiPF4(CF3)2, LiPF4(C2F5)2, Fluorine-containing organic lithium salts such as LiPF4(CF3SO2)2, LiPF4(C2F5SO2)2, LiBF3CF3, LiBF3C2F5, LiBF3C3F7, LiBF2(CF3)2, LiBF2(C2F5)2, LiBF2(CF3SO2)2, LiBF2(C2F5SO2)2; lithium oxalate borate salts such as lithium difluorooxalatoborate and lithium bis(oxalato)borate; lithium oxalate phosphate salts such as lithium tetrafluorooxalato phosphate, lithium difluorobis(oxalato) phosphate and lithium tris(oxalato) phosphate, etc.

[0150] In some embodiments, the electrolyte is selected from LiPF6, LiSbF6, FSO3Li, CF3SO3Li, LiN(FSO2)2, LiN(FSO2)(CF3SO2), LiN(CF3SO2)2, LiN(C2F5SO2)2, cyclic 1,2-perfluoroethane bissulfonyl imide lithium, cyclic 1,3-perfluoropropane bissulfonyl imide lithium, LiC(FSO2)3, LiC(CF3SO2)3, LiC(C2F5SO2)3, LiBF3CF3, LiBF3C2F5, LiPF3(CF3)3, LiPF3(C2F5)3, lithium difluorooxalatoborate, lithium bis(oxalate)borate or lithium difluorobis(oxalato)phosphate, which helps to improve the charge and discharge characteristics, high temperature storage characteristics and cycle characteristics of the electrochemical device.

[0151] The content of the electrolyte is not particularly limited as long as it does not impair the effect of the present application. In some embodiments, the total molar concentration of lithium in the electrolyte is greater than 0.3 mol / L, greater than 0.4 mol / L or greater than 0.5 mol / L. In some embodiments, the total molar concentration of lithium in the electrolyte is less than 3 mol / L, less than 2.5 mol / L or less than 2.0 mol / L. In some embodiments, the total molar concentration of lithium in the electrolyte is within the range formed by any two of the above values. When the electrolyte concentration is within the above range, there will not be too little lithium as a charged particle, and the viscosity can be kept within an appropriate range, thereby easily ensuring good conductivity.

[0152] When more than two electrolytes are used, the electrolyte includes at least one salt selected from the group consisting of monofluorophosphate, borate, oxalate and fluorosulfonate. In some embodiments, the electrolyte includes a salt selected from the group consisting of monofluorophosphate, oxalate and fluorosulfonate. In some embodiments, the electrolyte includes a lithium salt. In some embodiments, based on the weight of the electrolyte, the content of the salt selected from the group consisting of monofluorophosphate, borate, oxalate and fluorosulfonate is greater than 0.01% or greater than 0.1%. In some embodiments, based on the weight of the electrolyte, the content of the salt selected from the group consisting of monofluorophosphate, borate, oxalate and fluorosulfonate is less than 20% or less than 10%. In some embodiments, the content of the salt selected from the group consisting of monofluorophosphate, borate, oxalate and fluorosulfonate is within the range of any two of the above values.

[0153] In some embodiments, the electrolyte comprises one or more substances selected from the group consisting of monofluorophosphate, borate, oxalate and fluorosulfonate and one or more salts other than this. As salts other than this, the lithium salts exemplified above can be cited, and in some embodiments, they are LiPF6, LiN(FSO2)(CF3SO2), LiN(CF3SO2)2, LiN(C2F5SO2)2, cyclic 1,2-perfluoroethane bissulfonyl imide lithium, cyclic 1,3-perfluoropropane bissulfonyl imide lithium, LiC(FSO2)3, LiC(CF3SO2)3, LiC(C2F5SO2)3, LiBF3CF3, LiBF3C2F5, LiPF3(CF3)3, LiPF3(C2F5)3. In some embodiments, the salt other than this is LiPF6.

[0154] In some embodiments, the content of the other salt is greater than 0.01% or greater than 0.1% based on the weight of the electrolyte. In some embodiments, the content of the other salt is less than 20%, less than 15%, or less than 10% based on the weight of the electrolyte. In some embodiments, the content of the other salt is within the range formed by any two of the above values. The other salt having the above content helps to balance the conductivity and viscosity of the electrolyte.

[0155] In addition to the above-mentioned solvents, additives and electrolyte salts, the electrolyte may contain additional additives such as negative electrode film formers, positive electrode protective agents, and anti-overcharge agents as needed. As additives, additives generally used in non-aqueous electrolyte secondary batteries may be used, examples of which may include, but are not limited to, vinylene carbonate, succinic anhydride, biphenyl, cyclohexylbenzene, 2,4-difluoroanisole, propane sultone, propene sultone, and the like. These additives may be used alone or in any combination. In addition, the content of these additives in the electrolyte is not particularly limited and can be appropriately set according to the type of the additive, etc. In some embodiments, the content of the additive is less than 5%, in the range of 0.01% to 5%, or in the range of 0.2% to 5%, based on the weight of the electrolyte.

[0156] III. Positive electrode

[0157] The positive electrode includes a positive electrode current collector and a positive electrode active material layer disposed on one or both surfaces of the positive electrode current collector.

[0158] 1. Positive electrode active material layer

[0159] Positive electrode active material layer Positive electrode active material. The positive electrode active material layer may be one layer or multiple layers. Each layer of the multiple layers of positive electrode active material may contain the same or different positive electrode active materials. The positive electrode active material is any material that can reversibly embed and de-embed metal ions such as lithium ions.

[0160] There is no particular limitation on the type of positive electrode active material, as long as it can electrochemically absorb and release metal ions (e.g., lithium ions). In some embodiments, the positive electrode active material is a material containing lithium and at least one transition metal. Examples of positive electrode active materials may include, but are not limited to, lithium transition metal composite oxides and lithium-containing transition metal phosphate compounds.

[0161] In some embodiments, the transition metal in the lithium transition metal composite oxide includes V, Ti, Cr, Mn, Fe, Co, Ni, Cu, etc. In some embodiments, the lithium transition metal composite oxide includes lithium cobalt composite oxides such as LiCoO2, lithium nickel composite oxides such as LiNiO2, lithium manganese composite oxides such as LiMnO2, LiMn2O4, Li2MnO4, LiNi 1 / 3 Mn 1 / 3 Co 1 / 3 O2、LiNi 0.5 Mn 0.3 Co 0.2 O2 and the like, wherein a portion of the transition metal atoms serving as the main body of these lithium transition metal composite oxides are replaced by other elements such as Na, K, B, F, Al, Ti, V, Cr, Mn, Fe, Co, Li, Ni, Cu, Zn, Mg, Ga, Zr, Si, Nb, Mo, Sn, W, etc. Examples of lithium transition metal composite oxides may include, but are not limited to, LiNi 0.5 Mn 0.5 O2、LiNi 0.85 Co 0.10 Al 0.05 O2、LiNi 0.33 Co 0.33 Mn 0.33 O2、LiNi 0.45 Co 0.10 Al 0.45 O2、LiMn 1.8 Al 0.2 O4 and LiMn 1.5 Ni 0.5 O4, etc. Examples of combinations of lithium transition metal composite oxides include, but are not limited to, combinations of LiCoO2 and LiMn2O4, wherein a portion of the Mn in LiMn2O4 can be replaced by a transition metal (e.g., LiNi 0.33 Co 0.33 Mn 0.33O2), part of the Co in LiCoO2 can be replaced by transition metals.

[0162] In some embodiments, the transition metal in the lithium-containing transition metal phosphate compound includes V, Ti, Cr, Mn, Fe, Co, Ni, Cu, etc. In some embodiments, the lithium-containing transition metal phosphate compound includes iron phosphates such as LiFePO4, Li3Fe2(PO4)3, LiFeP2O7, and cobalt phosphates such as LiCoPO4, wherein a portion of the transition metal atoms as the main body of these lithium transition metal phosphate compounds are replaced by other elements such as Al, Ti, V, Cr, Mn, Fe, Co, Li, Ni, Cu, Zn, Mg, Ga, Zr, Nb, Si, etc.

[0163] In some embodiments, the positive electrode active material includes lithium phosphate, which can improve the continuous charging characteristics of the electrochemical device. There is no limitation on the use of lithium phosphate. In some embodiments, the positive electrode active material and lithium phosphate are mixed. In some embodiments, the content of lithium phosphate is greater than 0.1%, greater than 0.3% or greater than 0.5% relative to the weight of the above-mentioned positive electrode active material and lithium phosphate. In some embodiments, the content of lithium phosphate is less than 10%, less than 8% or less than 5% relative to the weight of the above-mentioned positive electrode active material and lithium phosphate. In some embodiments, the content of lithium phosphate is within the range formed by any two of the above-mentioned values.

[0164] surface coating

[0165] A substance having a different composition from that of the positive electrode active material may be attached to the surface of the positive electrode active material. Examples of the surface-attached substance may include, but are not limited to: oxides such as aluminum oxide, silicon dioxide, titanium dioxide, zirconium oxide, magnesium oxide, calcium oxide, boron oxide, antimony oxide, and bismuth oxide; sulfates such as lithium sulfate, sodium sulfate, potassium sulfate, magnesium sulfate, calcium sulfate, and aluminum sulfate; carbonates such as lithium carbonate, calcium carbonate, and magnesium carbonate; and carbon.

[0166] These surface-attached substances can be attached to the surface of the positive electrode active material by the following methods: a method in which the surface-attached substance is dissolved or suspended in a solvent and then added to the positive electrode active material and dried; a method in which a surface-attached substance precursor is dissolved or suspended in a solvent, added to the positive electrode active material, and then reacted by heating or the like; and a method in which the surface-attached substance is added to the positive electrode active material precursor and then fired simultaneously, etc. In the case of carbon attachment, a method in which a carbon material (e.g., activated carbon, etc.) is mechanically attached can also be used.

[0167] In some embodiments, the content of the surface-attached substance is greater than 0.1 ppm, greater than 1 ppm, or greater than 10 ppm based on the weight of the positive electrode active material layer. In some embodiments, the content of the surface-attached substance is less than 10%, less than 5%, or less than 2% based on the weight of the positive electrode active material layer. In some embodiments, the content of the surface-attached substance is within the range of any two of the above values ​​based on the weight of the positive electrode active material layer.

[0168] By attaching substances to the surface of the positive electrode active material, the oxidation reaction of the electrolyte on the surface of the positive electrode active material can be suppressed, and the life of the electrochemical device can be improved. When the amount of surface-attached substances is too small, the effect cannot be fully demonstrated; when the amount of surface-attached substances is too large, it will hinder the entry and exit of lithium ions, and the resistance may sometimes increase.

[0169] In the present application, a positive electrode active material in which a substance having a different composition from the positive electrode active material is attached to the surface of the positive electrode active material is also referred to as a “positive electrode active material”.

[0170] shape

[0171] In some embodiments, the shape of the positive electrode active material particles includes, but is not limited to, block, polyhedron, sphere, ellipsoid, plate, needle and column, etc. In some embodiments, the positive electrode active material particles include primary particles, secondary particles or a combination thereof. In some embodiments, the primary particles can be agglomerated to form secondary particles.

[0172] Tap density

[0173] In some embodiments, the tap density of the positive electrode active material is greater than 0.5 g / cm 3 , greater than 0.8g / cm 3 Or greater than 1.0g / cm 3 . When the tap density of the positive electrode active material is within the above range, the amount of dispersion medium and the required amount of conductive material and positive electrode binder required for the formation of the positive electrode active material layer can be suppressed, thereby ensuring the filling rate of the positive electrode active material and the capacity of the electrochemical device. By using a composite oxide powder with a high tap density, a high-density positive electrode active material layer can be formed. The larger the tap density, the better, and there is no particular upper limit. In some embodiments, the tap density of the positive electrode active material is less than 4.0 g / cm 3 , less than 3.7g / cm 3 or less than 3.5g / cm 3 When the tap density of the positive electrode active material has the upper limit as described above, a decrease in load characteristics can be suppressed.

[0174] The tap density of the positive electrode active material can be calculated by placing 5 g to 10 g of the positive electrode active material powder in a 10 mL glass measuring cylinder and vibrating the cylinder 200 times with a stroke of 20 mm to obtain the powder packing density (tap density).

[0175] Median particle size (D50)

[0176] When the positive electrode active material particles are primary particles, the median particle size (D50) of the positive electrode active material particles refers to the primary particle size of the positive electrode active material particles. When the primary particles of the positive electrode active material particles aggregate to form secondary particles, the median particle size (D50) of the positive electrode active material particles refers to the secondary particle size of the positive electrode active material particles.

[0177] In some embodiments, the median particle size (D50) of the positive electrode active material particles is greater than 0.3 μm, greater than 0.5 μm, greater than 0.8 μm or greater than 1.0 μm. In some embodiments, the median particle size (D50) of the positive electrode active material particles is less than 30 μm, less than 27 μm, less than 25 μm or less than 22 μm. In some embodiments, the median particle size (D50) of the positive electrode active material particles is within the range composed of any two of the above values. When the median particle size (D50) of the positive electrode active material particles is within the above range, a positive electrode active material with a high tap density can be obtained, which can inhibit the reduction of the performance of the electrochemical device. On the other hand, in the preparation process of the positive electrode of the electrochemical device (that is, when the positive electrode active material, the conductive material and the binder are slurried with a solvent and coated in a thin film), problems such as streaks can be prevented. Here, by mixing two or more positive electrode active materials with different median particle sizes, the filling property during the preparation of the positive electrode can be further improved.

[0178] The median particle size (D50) of the positive electrode active material particles can be measured using a laser diffraction / scattering particle size distribution measuring device: when using LA-920 manufactured by HORIBA as a particle size distribution meter, a 0.1% sodium hexametaphosphate aqueous solution is used as the dispersion medium used in the measurement, and the measurement refractive index is set to 1.24 after 5 minutes of ultrasonic dispersion.

[0179] Average primary particle size

[0180] In the case where the primary particles of the positive electrode active material particles agglomerate to form secondary particles, in some embodiments, the average primary particle size of the positive electrode active material is greater than 0.05 μm, greater than 0.1 μm or greater than 0.5 μm. In some embodiments, the average primary particle size of the positive electrode active material is less than 5 μm, less than 4 μm, less than 3 μm or less than 2 μm. In some embodiments, the average primary particle size of the positive electrode active material is within the range formed by any two of the above values. When the average primary particle size of the positive electrode active material is within the above range, the powder filling and specific surface area can be ensured, the reduction of battery performance can be suppressed, and appropriate crystallinity can be obtained, thereby ensuring the reversibility of charging and discharging of the electrochemical device.

[0181] The average primary particle size of the positive electrode active material can be obtained by observing the image obtained by scanning electron microscopy (SEM): in the SEM image with a magnification of 10,000 times, for any 50 primary particles, the longest value of the slice obtained by the left and right boundary lines of the primary particles relative to the horizontal straight line is calculated, and the average value is calculated to obtain the average primary particle size.

[0182] Specific surface area (BET)

[0183] In some embodiments, the specific surface area (BET) of the positive electrode active material is greater than 0.1 m 2 / g, greater than 0.2m 2 / g or greater than 0.3m 2 In some embodiments, the specific surface area (BET) of the positive electrode active material is less than 50 m 2 / g, less than 40m 2 / g or less than 30m 2 / g. In some embodiments, the specific surface area (BET) of the positive electrode active material is within the range formed by any two of the above values. When the specific surface area (BET) of the positive electrode active material is within the above range, the performance of the electrochemical device can be ensured, and the positive electrode active material can have good coating properties.

[0184] The specific surface area (BET) of the positive electrode active material can be measured by the following method: using a surface area meter (for example, a fully automatic surface area measuring device manufactured by Okura Riken), pre-drying the sample at 150°C for 30 minutes under nitrogen flow, and then using a nitrogen-helium mixed gas with a relative pressure value of nitrogen accurately adjusted to 0.3 relative to atmospheric pressure, the sample is measured by the nitrogen adsorption BET single-point method using the gas flow method.

[0185] Positive electrode conductive material

[0186] There is no limitation on the type of positive electrode conductive material, and any known conductive material can be used. Examples of positive electrode conductive materials may include, but are not limited to, graphite such as natural graphite and artificial graphite; carbon black such as acetylene black; carbon materials such as amorphous carbon such as needle coke; carbon nanotubes; graphene, etc. The above positive electrode conductive materials may be used alone or in any combination.

[0187] In some embodiments, the content of the positive electrode conductive material is greater than 0.01%, greater than 0.1%, or greater than 1%, based on the weight of the positive electrode active material layer. In some embodiments, the content of the positive electrode conductive material is less than 10%, less than 8%, or less than 5%, based on the weight of the positive electrode active material layer. When the content of the positive electrode conductive material is within the above range, sufficient conductivity and capacity of the electrochemical device can be ensured.

[0188] Positive electrode binder

[0189] There is no particular restriction on the type of positive electrode binder used in the manufacture of the positive electrode active material layer. In the case of a coating method, any material that can be dissolved or dispersed in the liquid medium used in the manufacture of the electrode can be used. Examples of positive electrode binders may include, but are not limited to, one or more of the following: resin polymers such as polyethylene, polypropylene, polyethylene terephthalate, polymethyl methacrylate, polyimide, aromatic polyamide, cellulose, and nitrocellulose; rubber polymers such as styrene-butadiene rubber (SBR), nitrile rubber (NBR), fluororubber, isoprene rubber, polybutadiene rubber, and ethylene-propylene rubber; styrene-butadiene-styrene block copolymers or their hydrogenates, ethylene-propylene-diene terpolymers (EPDM), Thermoplastic elastomer polymers such as styrene·ethylene·butadiene·ethylene copolymers, styrene·isoprene·styrene block copolymers or their hydrogenated products; soft resin polymers such as syndiotactic-1,2-polybutadiene, polyvinyl acetate, ethylene·vinyl acetate copolymers, propylene·α-olefin copolymers; fluorine-based polymers such as polyvinylidene fluoride (PVDF), polytetrafluoroethylene, fluorinated polyvinylidene fluoride, polytetrafluoroethylene·ethylene copolymers; polymer compositions having ion conductivity of alkali metal ions (especially lithium ions), etc. The above positive electrode binders can be used alone or in any combination.

[0190] In some embodiments, the content of the positive electrode binder is greater than 0.1%, greater than 1%, or greater than 1.5%, based on the weight of the positive electrode active material layer. In some embodiments, the content of the positive electrode binder is less than 10%, less than 5%, less than 4%, or less than 3%, based on the weight of the positive electrode active material layer. When the content of the positive electrode binder is within the above range, the positive electrode can have good conductivity and sufficient mechanical strength, and the capacity of the electrochemical device is guaranteed.

[0191] Solvents

[0192] There is no limitation on the type of solvent used to form the positive electrode slurry, as long as it is a solvent that can dissolve or disperse the positive electrode active material, the conductive material, the positive electrode binder, and the thickener used as needed. Examples of solvents used to form the positive electrode slurry may include any of aqueous solvents and organic solvents. Examples of aqueous media may include, but are not limited to, water and mixed media of alcohol and water. Examples of organic media may include, but are not limited to, aliphatic hydrocarbons such as hexane; aromatic hydrocarbons such as benzene, toluene, xylene, methylnaphthalene; heterocyclic compounds such as quinoline and pyridine; ketones such as acetone, methyl ethyl ketone, and cyclohexanone; esters such as methyl acetate and methyl acrylate; amines such as diethylenetriamine and N,N-dimethylaminopropylamine; ethers such as diethyl ether, propylene oxide, and tetrahydrofuran (THF); amides such as N-methylpyrrolidone (NMP), dimethylformamide, and dimethylacetamide; aprotic polar solvents such as hexamethylphosphoramide and dimethyl sulfoxide, etc.

[0193] Thickener

[0194] Thickeners are generally used to adjust the viscosity of the slurry. In the case of using an aqueous medium, a thickener and a styrene-butadiene rubber (SBR) emulsion can be used for slurrying. The type of thickener is not particularly limited, and examples thereof may include, but are not limited to, carboxymethyl cellulose, methyl cellulose, hydroxymethyl cellulose, ethyl cellulose, polyvinyl alcohol, oxidized starch, phosphorylated starch, casein, and salts thereof. The above thickeners may be used alone or in any combination.

[0195] In some embodiments, the content of the thickener is greater than 0.1%, greater than 0.2%, or greater than 0.3% based on the weight of the positive electrode active material layer. In some embodiments, the content of the thickener is less than 5%, less than 3%, or less than 2% based on the weight of the positive electrode active material layer. In some embodiments, the content of the thickener is within the range of any two of the above values ​​based on the weight of the positive electrode active material layer. When the content of the thickener is within the above range, the positive electrode slurry can have good coating properties, and the capacity reduction and resistance increase of the electrochemical device can be suppressed.

[0196] Content of positive electrode active material

[0197] In some embodiments, the content of the positive electrode active material is greater than 80%, greater than 82%, or greater than 84% based on the weight of the positive electrode active material layer. In some embodiments, the content of the positive electrode active material is less than 99% or less than 98% based on the weight of the positive electrode active material layer. In some embodiments, the content of the positive electrode active material is within the range of any two arrays above based on the weight of the positive electrode active material layer. When the content of the positive electrode active material is within the above range, the capacitance of the positive electrode active material in the positive electrode active material layer can be ensured, and the strength of the positive electrode can be maintained.

[0198] Density of the positive electrode active material layer

[0199] The positive electrode active material layer obtained by coating and drying may be compacted by a manual press or a roller press to increase the packing density of the positive electrode active material. In some embodiments, the density of the positive electrode active material layer is greater than 1.5 g / cm 3 , greater than 2g / cm 3 or greater than 2.2g / cm 3 In some embodiments, the density of the positive electrode active material layer is less than 5 g / cm 3 , less than 4.5g / cm 3 or less than 4g / cm 3 In some embodiments, the density of the positive electrode active material layer is within the range formed by any two of the above values. When the density of the positive electrode active material layer is within the above range, the electrochemical device can have good charge and discharge characteristics, while suppressing the increase of resistance.

[0200] Thickness of positive electrode active material layer

[0201] The thickness of the positive electrode active material layer refers to the thickness of the positive electrode active material layer on either side of the positive electrode current collector. In some embodiments, the thickness of the positive electrode active material layer is greater than 10 μm or greater than 20 μm. In some embodiments, the thickness of the positive electrode active material layer is less than 500 μm or less than 450 μm.

[0202] Method for producing positive electrode active material

[0203] The positive electrode active material can be manufactured using a common method for manufacturing inorganic compounds. In order to make a spherical or ellipsoidal positive electrode active material, the following manufacturing method can be used: dissolve or crush the raw material of the transition metal and disperse it in a solvent such as water, adjust the pH while stirring, make a spherical precursor and recover it, dry it as needed, add a Li source such as LiOH, Li2CO3, LiNO3, and sinter it at a high temperature to obtain a positive electrode active material.

[0204] 2. Positive electrode current collector

[0205] The type of positive electrode current collector is not particularly limited, and it can be any material known to be suitable for use as a positive electrode current collector. Examples of positive electrode current collectors may include, but are not limited to, metal materials such as aluminum, stainless steel, nickel plating, titanium, tantalum, and carbon materials such as carbon cloth and carbon paper. In some embodiments, the positive electrode current collector is a metal material. In some embodiments, the positive electrode current collector is aluminum.

[0206] There is no particular restriction on the form of the positive electrode current collector. When the positive electrode current collector is a metal material, the form of the positive electrode current collector may include, but is not limited to, metal foil, metal cylinder, metal strip roll, metal plate, metal foil, metal plate mesh, stamped metal, foamed metal, etc. When the positive electrode current collector is a carbon material, the form of the positive electrode current collector may include, but is not limited to, carbon plate, carbon film, carbon cylinder, etc. In some embodiments, the positive electrode current collector is a metal foil. In some embodiments, the metal foil is mesh-shaped. The thickness of the metal foil is not particularly limited. In some embodiments, the thickness of the metal foil is greater than 1 μm, greater than 3 μm, or greater than 5 μm. In some embodiments, the thickness of the metal foil is less than 1 mm, less than 100 μm, or less than 50 μm. In some embodiments, the thickness of the metal foil is within the range composed of any two of the above values.

[0207] In order to reduce the electronic contact resistance between the positive electrode current collector and the positive electrode active material layer, the surface of the positive electrode current collector may include a conductive additive. Examples of the conductive additive may include, but are not limited to, carbon and precious metals such as gold, platinum, and silver.

[0208] The thickness ratio of the positive electrode active material layer to the positive electrode current collector refers to the thickness of the single-sided positive electrode active material layer divided by the thickness of the positive electrode current collector, and its value is not particularly limited. In some embodiments, the thickness ratio is less than 50, less than 30, or less than 20. In some embodiments, the thickness ratio is greater than 0.5, greater than 0.8, or greater than 1. In some embodiments, the thickness ratio is within the range of any two of the above values. When the thickness ratio is within the above range, the heat release of the positive electrode current collector during high current density charging and discharging can be suppressed, and the capacity of the electrochemical device can be ensured.

[0209] 3. Method of making positive electrode

[0210] The positive electrode can be made by forming a positive electrode active material layer containing a positive electrode active material and a binder on a current collector. The manufacture of a positive electrode using a positive electrode active material can be carried out by a conventional method, that is, the positive electrode active material and the binder, as well as the conductive material and the thickener as required, are dry-mixed to form a sheet, and the obtained sheet is pressed onto the positive electrode current collector; or these materials are dissolved or dispersed in a liquid medium to form a slurry, and the slurry is applied to the positive electrode current collector and dried to form a positive electrode active material layer on the current collector, thereby obtaining a positive electrode.

[0211] IV. Isolation membrane

[0212] In order to prevent short circuit, a separator is usually provided between the positive electrode and the negative electrode. In this case, the electrolyte of the present application is usually used by infiltrating the separator.

[0213] There is no particular restriction on the material and shape of the isolation membrane, as long as the effect of the present application is not significantly impaired. The isolation membrane may be a resin, glass fiber, inorganic substance, etc. formed of a material that is stable to the electrolyte of the present application. In some embodiments, the isolation membrane includes a porous sheet or a non-woven fabric-like material with excellent liquid retention. Examples of materials for resin or glass fiber isolation membranes may include, but are not limited to, polyolefins, aromatic polyamides, polytetrafluoroethylene, polyether sulfone, etc. In some embodiments, the polyolefin is polyethylene or polypropylene. In some embodiments, the polyolefin is polypropylene. The materials of the above isolation membranes may be used alone or in any combination.

[0214] The isolation film may also be a material formed by laminating the above materials, and examples thereof include, but are not limited to, a three-layer isolation film formed by laminating polypropylene, polyethylene, and polypropylene in this order.

[0215] Examples of inorganic materials may include, but are not limited to, oxides such as aluminum oxide and silicon dioxide, nitrides such as aluminum nitride and silicon nitride, and sulfates (e.g., barium sulfate, calcium sulfate, etc.) The form of the inorganic material may include, but is not limited to, granular or fibrous.

[0216] The separator may be in the form of a thin film, examples of which include, but are not limited to, nonwoven fabrics, woven fabrics, microporous films, etc. In the thin film form, the separator has a pore size of 0.01 μm to 1 μm and a thickness of 5 μm to 50 μm. In addition to the above-mentioned independent thin film separators, the following separators may also be used: a separator formed by forming a composite porous layer containing the above-mentioned inorganic particles on the surface of the positive electrode and / or the negative electrode using a resin-based adhesive, for example, a separator formed by using a fluororesin as an adhesive to form a porous layer on both sides of the positive electrode with aluminum oxide particles having a particle size of 90% less than 1 μm.

[0217] The thickness of the isolation membrane is arbitrary. In some embodiments, the thickness of the isolation membrane is greater than 1 μm, greater than 5 μm, or greater than 8 μm. In some embodiments, the thickness of the isolation membrane is less than 50 μm, less than 40 μm, or less than 30 μm. In some embodiments, the thickness of the isolation membrane is within the range formed by any two of the above values. When the thickness of the isolation membrane is within the above range, the insulation and mechanical strength can be ensured, and the rate characteristics and energy density of the electrochemical device can be ensured.

[0218] When a porous material such as a porous sheet or non-woven fabric is used as an isolation membrane, the porosity of the isolation membrane is arbitrary. In some embodiments, the porosity of the isolation membrane is greater than 10%, greater than 15%, or greater than 20%. In some embodiments, the porosity of the isolation membrane is less than 60%, less than 50%, or less than 45%. In some embodiments, the porosity of the isolation membrane is within the range formed by any two of the above values. When the porosity of the isolation membrane is within the above range, insulation and mechanical strength can be ensured, and membrane resistance can be suppressed, so that the electrochemical device has good safety characteristics.

[0219] The average pore size of the isolation membrane is also arbitrary. In some embodiments, the average pore size of the isolation membrane is less than 0.5 μm or less than 0.2 μm. In some embodiments, the average pore size of the isolation membrane is greater than 0.05 μm. In some embodiments, the average pore size of the isolation membrane is within the range formed by any two of the above values. If the average pore size of the isolation membrane exceeds the above range, short circuit is likely to occur. When the average pore size of the isolation membrane is within the above range, the electrochemical device has good safety characteristics.

[0220] V. Electrochemical Device Components

[0221] The electrochemical device assembly includes an electrode group, a current collecting structure, an outer casing and a protective element.

[0222] Electrode Group

[0223] The electrode group may be any of a laminated structure formed by laminating the above-mentioned positive electrode and the negative electrode with the above-mentioned separator, and a structure formed by spirally winding the above-mentioned positive electrode and the negative electrode with the above-mentioned separator. In some embodiments, the proportion of the mass of the electrode group in the internal volume of the battery (electrode group occupancy) is greater than 40% or greater than 50%. In some embodiments, the electrode group occupancy is less than 90% or less than 80%. In some embodiments, the electrode group occupancy is within the range formed by any two of the above values. When the electrode group occupancy is within the above range, the capacity of the electrochemical device can be ensured, and at the same time, the reduction of characteristics such as repeated charge and discharge performance and high temperature storage associated with the increase in internal pressure can be suppressed.

[0224] Current collection structure

[0225] There is no particular limitation on the current collection structure. In some embodiments, the current collection structure is a structure that reduces the resistance of the wiring portion and the joint portion. When the electrode group is the above-mentioned stacked structure, it is suitable to use a structure formed by bundling the metal core portions of each electrode layer and welding them to the terminal. When the electrode area of ​​a sheet increases, the internal resistance increases, so it is also suitable to set more than two terminals in the electrode to reduce the resistance. When the electrode group is the above-mentioned winding structure, the internal resistance can be reduced by setting more than two lead structures at the positive electrode and the negative electrode respectively, and bundling them at the terminal.

[0226] External shell

[0227] The material of the outer casing is not particularly limited, as long as it is a material that is stable to the electrolyte used. The outer casing can be made of, but not limited to, nickel-plated steel, stainless steel, aluminum or aluminum alloy, magnesium alloy and other metals, or a laminated film of resin and aluminum foil. In some embodiments, the outer casing is a metal or laminated film of aluminum or aluminum alloy.

[0228] The metal outer casing includes, but is not limited to, a packaged closed structure formed by welding metals to each other by laser welding, resistance welding, and ultrasonic welding; or a riveted structure formed by using the above-mentioned metals through a resin gasket. The outer casing using the above-mentioned laminated film includes, but is not limited to, a packaged closed structure formed by thermally bonding resin layers to each other. In order to improve the sealing performance, a resin different from the resin used in the laminated film can also be sandwiched between the above-mentioned resin layers. When the resin layer is thermally bonded to form a closed structure through the collector terminal, due to the bonding between the metal and the resin, a resin with a polar group or a modified resin into which a polar group is introduced can be used as the sandwiched resin. In addition, the shape of the outer casing is also arbitrary, for example, it can be any of cylindrical, square, laminated, button-shaped, large, etc.

[0229] Protection components

[0230] The protection element may be a positive temperature coefficient (PTC) whose resistance increases when abnormal heat is released or excessive current flows, a temperature fuse, a thermistor, or a valve (current cutoff valve) that cuts off the current flowing in the circuit by causing the internal pressure or internal temperature of the battery to rise sharply when abnormal heat is released. The above protection element may be selected to be an element that does not work in normal use of high current, or may be designed in a form that does not cause abnormal heat release or thermal runaway even if the protection element is not present.

[0231] VI. Application

[0232] The electrochemical device of the present application includes any device that generates an electrochemical reaction, and its specific examples include all kinds of primary batteries, secondary batteries, fuel cells, solar cells or capacitors. In particular, the electrochemical device is a lithium secondary battery, including a lithium metal secondary battery or a lithium ion secondary battery.

[0233] The present application further provides an electronic device, which includes the electrochemical device according to the present application.

[0234] The use of the electrochemical device of the present application is not particularly limited, and it can be used for any electronic device known in the prior art. In some embodiments, the electrochemical device of the present application can be used for, but not limited to, laptop computers, pen-input computers, mobile computers, e-book players, portable phones, portable fax machines, portable copiers, portable printers, head-mounted stereo headphones, video recorders, LCD televisions, portable cleaners, portable CD players, mini-discs, transceivers, electronic notepads, calculators, memory cards, portable recorders, radios, backup power supplies, motors, cars, motorcycles, power-assisted bicycles, bicycles, lighting fixtures, toys, game consoles, clocks, power tools, flashlights, cameras, large household batteries and lithium-ion capacitors, etc.

[0235] The preparation of lithium-ion batteries is described below by taking lithium-ion batteries as an example and combining specific embodiments. Those skilled in the art will understand that the preparation method described in this application is only an example, and any other suitable preparation method is within the scope of this application.

[0236] Example

[0237] The following describes the performance evaluation of the examples and comparative examples of the lithium-ion battery according to the present application.

[0238] 1. Preparation of lithium-ion batteries

[0239] 1. Preparation of negative electrode

[0240] According to the comparative example and the embodiment, the conductive material, the binder (when the conductive material is present, the mass ratio of the conductive material to the binder is 64.5%:35.5%) and deionized water are mixed and stirred evenly to obtain a first slurry. The first slurry is coated on the copper foil.

[0241] Artificial graphite, styrene-butadiene rubber and sodium carboxymethyl cellulose are mixed with deionized water in a mass ratio of 96%:2%:2%, and stirred evenly to obtain a second slurry. The second slurry is coated on the copper foil loaded with the first slurry. Drying, cold pressing, cutting and welding of the tabs are performed to obtain a negative electrode.

[0242] 2. Preparation of positive electrode

[0243] Lithium cobalt oxide (LiCoO2), conductive material (Super-P) and polyvinylidene fluoride (PVDF) were mixed with N-methylpyrrolidone (NMP) in a mass ratio of 95%:2%:3%, and stirred evenly to obtain a positive electrode slurry. The positive electrode slurry was coated on a 12μm aluminum foil, dried, cold pressed, and then cut and welded to the tabs to obtain a positive electrode.

[0244] 3. Preparation of electrolyte

[0245] In a dry argon environment, EC, PC and DEC (weight ratio 1:1:1) were mixed, and LiPF6 was added and mixed evenly to form a basic electrolyte, wherein the concentration of LiPF6 was 1.15 mol / L. Different amounts of additives were added to the basic electrolyte to obtain electrolytes of different embodiments and comparative examples.

[0246] The abbreviations and names of the components in the electrolyte are shown in the following table:

[0247] Material Name abbreviation Material Name abbreviation Ethylene carbonate EC Propylene carbonate PC Ethyl methyl carbonate EMC Ethyl propionate EP Propyl Propionate PP Adiponitrile ADN Succinonitrile SN 1,3,6-Hexanetrinitrile HTCN Ethylene glycol di(2-cyanoethyl) ether EDN Lithium difluorophosphate <![CDATA[LiPO2F2]]> 1,2,3-Tris(2-cyanoethoxy)propane TCEP 1,2-Ethylene glycol sulfate DTD 1,3-Propane sultone PS Compound of formula 1-2 Formula 1-2 Compound of formula 1-1 Formula 1-1

[0248] 4. Preparation of isolation membrane

[0249] A polyethylene (PE) porous polymer film is used as the isolation membrane.

[0250] 5. Preparation of lithium-ion batteries

[0251] The obtained positive electrode, separator and negative electrode are wound in order and placed in an outer packaging foil, leaving a liquid injection port. The electrolyte is poured from the liquid injection port, packaged, and then subjected to formation, capacity and other processes to obtain a lithium-ion battery.

[0252] 2. Test Method

[0253] 1. Test method for cycle expansion rate of lithium-ion batteries

[0254] At 55°C, let the lithium-ion battery stand for 30 minutes, then charge it to 4.45V at a constant current rate of 0.5C, then charge it to 0.05C at a constant voltage rate at 4.45V, let it stand for 5 minutes, and measure the thickness of the lithium-ion battery. Cycle 100 times under the same conditions as above, and measure the thickness of the lithium-ion battery after the cycle. The high-temperature cycle expansion rate of the lithium-ion battery is calculated by the following formula:

[0255] High temperature cycle expansion ratio = [(thickness after cycle - thickness before cycle) / thickness before cycle] × 100%.

[0256] 2. Test method for overcharge deformation rate of lithium-ion batteries

[0257] At 25°C, the lithium-ion battery was allowed to stand for 30 minutes, then charged to 4.45V at a constant current rate of 0.5C, then charged to 0.05C at a constant voltage rate of 4.45V, allowed to stand for 60 minutes, and the thickness T1 of the lithium-ion battery was measured. Then, the lithium-ion battery was charged at a constant current rate of 0.1C for 60 minutes, allowed to stand for 30 minutes, and this step was repeated 5 times to make the lithium-ion battery reach a 150% state of charge (SOC), and the thickness T2 of the lithium-ion battery was measured.

[0258] Overcharge deformation rate = [(T2-T1) / T1]×100%.

[0259] 3. Test Results

[0260] Table 1 shows the weight of the conductive material and the negative electrode active material layer W mg / cm 2 Effects on high temperature cycle expansion rate and overcharge deformation rate of lithium ion batteries In the comparative examples and embodiments listed in Table 1, the D50 of the negative electrode active material is 15 μm, and styrene-butadiene rubber (SBR) is used as a binder.

[0261] Table 1

[0262]

[0263] “ / ” means that the feature is not added or not available

[0264] The results show that when there is a conductive material between the negative electrode active material layer and the negative electrode current collector, the average particle size of the conductive material is smaller than the average particle size of the negative electrode active material, and the weight per unit area of ​​the negative electrode active material layer is 3 mg / cm 2 Up to 12mg / cm 2 When the average particle size of the conductive material is less than 1 μm, the high temperature cycle expansion rate and overcharge deformation rate of the lithium ion battery can be further reduced.

[0265] Table 2 shows the influence of the tensile strength of the negative electrode current collector and the density of the negative electrode active material layer or the weight of the negative electrode active material layer on the high temperature cycle expansion rate and overcharge deformation rate of the lithium ion battery performance. The difference between Examples 2-1 to 2-14 and Example 1-1 is only the parameters listed in Table 2.

[0266] Table 2

[0267]

[0268]

[0269] The results show that when the tensile strength of the negative electrode current collector is FN / mm 2(F≥400), density of negative electrode active material layer Dg / cm 3 (D is 1.4 to 2.0) and the weight per unit area of ​​the negative electrode active material layer W mg / cm 2 When 100 / 3≤F / W≤150 and / or 560≤F×D≤1800 are satisfied, the high temperature cycle expansion rate and overcharge deformation rate of the lithium-ion battery can be further reduced.

[0270] Table 3 shows the effect of electrolyte components on the high temperature cycle expansion rate and overcharge deformation rate of lithium ion batteries. The difference between Examples 3-1 to 3-31 and Example 1-1 is only the parameters listed in Table 3.

[0271] Table 3

[0272]

[0273]

[0274] “ / ” means that the feature is not added or not available

[0275] The results show that there is a tiny conductive material between the negative electrode active material layer and the negative electrode current collector and the weight per unit area of ​​the negative electrode active material layer is 3 mg / cm 2 Up to 12mg / cm 2 On the basis of, when the electrolyte contains propionate, an organic compound having a cyano group, lithium difluorophosphate and / or the compound of Formula 1, the high temperature cycle expansion rate and overcharge deformation rate of the lithium ion battery can be further reduced.

[0276] Table 4 shows the content of organic compound having cyano group (a%) and the weight per unit area of ​​negative electrode active material layer (FN / mm) 2 The relationship between and affects the high temperature cycle expansion rate and overcharge deformation rate of lithium ion batteries. The difference between Examples 4-1 to 4-9 and Example 1-1 is only the parameters listed in Table 4.

[0277] Table 4

[0278]

[0279] The results show that when the content of the organic compound having a cyano group is a% and the weight per unit area of ​​the negative electrode active material layer is FN / mm 2 When 0.3≤W / a≤20 is met, the high temperature cycle expansion rate and overcharge deformation rate of the lithium-ion battery can be further reduced.

[0280] Table 5 shows the effect of the binder between the negative electrode current collector and the negative electrode active material layer on the high temperature cycle expansion rate and overcharge deformation rate of the lithium ion battery. The difference between Examples 5-1 to 5-5 and Example 1-1 is only the parameters listed in Table 5.

[0281] Table 5

[0282] Adhesives Decomposition temperature High temperature cycle expansion rate Overcharge deformation rate Example 1-1 Styrene-butadiene rubber 300℃ 12.2% 10.1% Example 5-1 Hydroxyethyl chitosan 160℃ 8.6% 8.5% Example 5-2 Hydroxypropyl Chitosan 180℃ 7.2% 7.9% Example 5-3 Hydroxybutyl chitosan 200℃ 6.7% 7.1% Example 5-4 Ethylene glycol dimethacrylate 210℃ 5.8% 6.9% Example 5-5 Propylene glycol dimethacrylate 220℃ 5.5% 6.5%

[0283] The results show that when an organic binder that can evaporate or decompose at a certain temperature is used, especially when the decomposition temperature is in the range of 160°C to 300°C, the high-temperature cycle expansion rate and overcharge deformation rate of lithium-ion batteries can be further reduced.

[0284] References to "embodiments", "partial embodiments", "one embodiment", "another example", "example", "specific example" or "partial example" throughout the specification mean that at least one embodiment or example in the present application includes the specific features, structures, materials or characteristics described in the embodiment or example. Therefore, descriptions appearing in various places throughout the specification, such as: "in some embodiments", "in an embodiment", "in one embodiment", "in another example", "in an example", "in a specific example" or "example", do not necessarily refer to the same embodiment or example in the present application. In addition, the specific features, structures, materials or characteristics herein may be combined in one or more embodiments or examples in any suitable manner.

[0285] Although illustrative embodiments have been demonstrated and described, those skilled in the art should understand that the above embodiments should not be construed as limitations on the present application, and that changes, substitutions and modifications may be made to the embodiments without departing from the spirit, principles and scope of the present application.

Claims

1. An electrochemical device comprising: A positive electrode, a negative electrode and an electrolyte, wherein the negative electrode comprises a negative electrode current collector and a negative electrode active material layer formed on the negative electrode current collector, wherein the negative electrode active material layer comprises a negative electrode active material, wherein: A conductive material is provided between the negative electrode active material layer and the negative electrode current collector, wherein the average particle size of the conductive material is smaller than the average particle size of the negative electrode active material, and the conductive material comprises at least one of carbon black, carbon fiber, graphene or carbon nanotube; The weight per unit area of ​​the negative electrode active material layer is W mg / cm 2 , W is in the range of 3 to 12; The tensile strength of the negative electrode current collector is FN / mm 2 The density of the negative electrode active material layer is Dg / cm 3 , D is in the range of 1.4 to 2.0 and 560≤F×D≤1800. 2 . The electrochemical device according to claim 1 , wherein the average particle size of the conductive material is 1 μm or less. 3 . The electrochemical device according to claim 1 , wherein a binder is further included between the negative electrode active material layer and the negative electrode current collector.

4. The electrochemical device according to claim 3, wherein the binder comprises at least one of styrene-butadiene rubber, styrene-butyl acrylate copolymer, styrene-(meth)acrylate copolymer, carboxymethyl cellulose, polyvinyl alcohol, sodium polyacrylate, polyvinylidene fluoride, polyimide, polyamideimide or deacetylated chitosan. The electrochemical device according to claim 3 , wherein the binder comprises an evaporable or decomposable organic binder.

6. The electrochemical device according to claim 5, wherein the organic binder comprises at least one of chitin-chitosan derivatives, fluorine-containing resins, synthetic rubbers, polyamides, polyimides, polyolefins, or polyacrylic resins. The electrochemical device according to claim 1 , wherein F is 400 or more and 100 / 3≤F / W≤150.

8. The electrochemical device according to claim 1, wherein the electrolyte comprises at least one of the following compounds: (a) Propionate esters; (b) organic compounds having a cyano group; (c) lithium difluorophosphate; (d) Compound of formula 1: in: R 1 , R 2 , R 3 , R 4 , R 5 and R 6 are independently hydrogen or C1-C 10 alkyl; L1 and L2 are each independently -(CR 7 R 8 ) n -; R 7 and R 8 are independently hydrogen or C1-C 10 Alkyl; and n is 1, 2 or 3.

9. The electrochemical device according to claim 8, wherein the compound of formula 1 comprises at least one of the following compounds: 10 . The electrochemical device according to claim 8 , wherein the content of the organic compound having a cyano group is a %, based on the weight of the electrolyte, and a is in the range of 0.1 to 10.

11. The electrochemical device according to claim 10, wherein W and a satisfy: 0.3≤W / a≤20.

12. An electronic device comprising the electrochemical device according to any one of claims 1 to 11.

Citation Information

Patent Citations

  • Quick-charging type lithium-ion battery and preparation method thereof

    CN108428867A

  • Negative electrode and electrochemical device and electronic device including same

    CN111146428A

  • Nonaqueous electrolyte, and nonaqueous electrolyte secondary battery using the same

    JP2011049152A

  • Nonaqueous electrolyte for secondary battery and nonaqueous-electrolyte secondary battery employing the same

    US20100119956A1